2011
DOI: 10.1128/mcb.00840-10
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mammalian Complex Containing Sin3B Mitigates Histone Acetylation and RNA Polymerase II Progression within Transcribed Loci

Abstract: Transcription requires the progression of RNA polymerase II (RNAP II) through a permissive chromatin structure. Recent studies of Saccharomyces cerevisiae have demonstrated that the yeast Sin3 protein contributes to the restoration of the repressed chromatin structure at actively transcribed loci. Yet, the mechanisms underlying the restoration of the repressive chromatin structure at transcribed loci and its significance in gene expression have not been investigated in mammals. We report here the identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
89
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 45 publications
10
89
0
Order By: Relevance
“…However, our transcriptomic analysis failed to identify potential intermediate factors that positively regulate Il1a levels, while being repressed by SIN3B. An alternative explanation for this positive regulation of IL-1α by SIN3B may stem from our recent observation that SIN3B participates in the release of polymerase pausing at active promoters, thus modulating the levels of actively transcribed genes (51).…”
Section: Discussionmentioning
confidence: 42%
“…However, our transcriptomic analysis failed to identify potential intermediate factors that positively regulate Il1a levels, while being repressed by SIN3B. An alternative explanation for this positive regulation of IL-1α by SIN3B may stem from our recent observation that SIN3B participates in the release of polymerase pausing at active promoters, thus modulating the levels of actively transcribed genes (51).…”
Section: Discussionmentioning
confidence: 42%
“…1D, lane 2), Sin3 remains associated with the rest of the subunits of Rpd3S. Lastly, Ume1 seems to only contact Sin3, and its absence does not influence other components of Rpd3S, which may explain the fact that no obvious ortholog has been found in flies and mammals (36,37).…”
Section: Rpd3s Contains Two Copies Of Rco1 As Revealed By Subunitintementioning
confidence: 98%
“…Two key components of Rpd3S that were shown to involve chromatin recognition are Eaf3, which contains a chromodomain (CHD) that binds to H3K36me, and Rco1, which contains two PHD domains with PHD1 being essential for Rpd3S function (11). All Rpd3S complexes that have been reported appear to function at coding regions where H3K36me is enriched, although the functional consequences of the resulting hypoacetylation at coding regions vary among species (22,36,37). We recently showed that Rpd3S prefers dinucleosome substrates and bridges between two linked nucleosomes (38).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the larger 1.2-to 2-MDa mammalian Sin3L/Rpd3L complex comprising seven unique subunits and at least as many paralogs is recruited to the promoter regions of genes by sequence-specific DNA-binding transcription factors, the smaller 0.5-to 0.6-MDa Sin3S/Rpd3S complex comprising five unique subunits and at least three paralogs is targeted to the intragenic regions of actively transcribed genes through interactions with specific chromatin signals (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Both complexes share Sin3A/B, HDAC1/2, and RBBP4/7 subunits and rely largely on HDAC activity to affect transcriptional repression; we note that there is now increasing evidence that Sin3A and Sin3B partition into the Sin3L/ Rpd3L and Sin3S/Rpd3S complexes, respectively (20,23).…”
mentioning
confidence: 99%